2011
DOI: 10.1093/ajae/aar133
|View full text |Cite
|
Sign up to set email alerts
|

World Food Demand

Abstract: Long‐term projections of global food demand are heavily dependent on which functional form of the food demand equation is used. Given that real incomes can change substantially over the long‐term, key elements are the dependence of the income elasticity on income, which ensures that the food budget share always lies within the [0, 1] range, and the role of income inequality. This article analyzes these issues, proposes a new functional form that deals with them, and presents estimates of income and price elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 62 publications
0
34
0
2
Order By: Relevance
“…Numerous studies have found η < 1, the classic reference being Houthakker (). Table provides information on incomes and food in a large number of countries in 2005, from Gao (). As per capita income falls (as we go down the table) the food share has a strong tendency to rise, in agreement with Engel’s law; and in all cases, the income elasticity is less than unity.…”
Section: Law 1: Engel’s Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have found η < 1, the classic reference being Houthakker (). Table provides information on incomes and food in a large number of countries in 2005, from Gao (). As per capita income falls (as we go down the table) the food share has a strong tendency to rise, in agreement with Engel’s law; and in all cases, the income elasticity is less than unity.…”
Section: Law 1: Engel’s Lawmentioning
confidence: 99%
“…14 A partial listing of the major studies on the income and price sensitivity of demand, each dealing with a large number of countries, includes Chen (1999), Gao (2012), Goldberger and Gamaletsos (1970), Houthakker (1957), Liu (2018), Lluch and Powell (1975), Lluch et al (1977), Muhammad et al (2013), Regmi and Seale (2010), Rimmer and Powell (1992), Seale and Regmi (2006), Seale et al (2003), Selvanathan (1993), Selvanathan and Selvanathan (2003), Theil and Clements (1987) and Theil et al (1981Theil et al ( , 1989. 15 Popular demand models are the linear expenditure system (Stone, 1954), the Rotterdam model (Barten, 1964;Theil, 1965), the almost ideal model and its quadratic extension (Deaton & Muellbauer, 1980a;Banks et al, 1997) and the translog model (Christensen et al, 1975).…”
mentioning
confidence: 99%
“…We treat the values of the seven income elasticities η 1 , …, η 7 and the income flexibility as unknown. The income elasticities of the food items are a weighted average of the income elasticity of all food ( η F ), available from Gao (): truetrue∑i=17()wiWFηi=ηF, where WF=Σi=17wi is the budget share of all food. Equation for i , j = 1, … 7 is a system of 49 equations, which is overdetermined and has no exact unique solution.…”
Section: Application To Foodmentioning
confidence: 99%
“…As incomes rise in lower income countries, their food expenditures grow and consumption patterns appear to seek to catch up to the levels and composition of those of higher income countries (Regmi, Meade, 2013). In low-income countries, expenditure on foods can take up to 62% of income, and in middle-income and high-income countries, people spend on average much less on foods (6-30% of their income) (Gao, 2012). In the middle-income and high-income countries, a similar increase in food prices is likely to have a much smaller impact on consumption.…”
Section: Literature Overviewmentioning
confidence: 99%